When destination attractiveness shifts in response to climate change: tourists' adaptation intention in Taiwan's Kenting National Park. Issue 5 (16th March 2019) - Wang, Wei-Ching; Lin, Chung-Hsien; Lu, Wen-Bor; Lee, Su-Hsin
ABSTRACT: We tested a structural model that integrates protection motivation theory with the individual's (farmer's) climate change adaptation process. The model helps us grasp the effects of climate change perception and hypothetical shifts in destination attractiveness, as well as threat and coping appraisals in light of tourists' adaptation intentions in coastal destinations. We collected a total of 333 on-site valid questionnaires from domestic tourists at Kenting National Park in Taiwan and analysed the structural relationships in the aforementioned study constructs using structural equation modelling. Our findings show that when tourists have a higher level of perception regarding global climate change, they believe that destination attractiveness will decrease. When presented with scenarios of hypothetical shifts in destination attractiveness, tourists with higher levels of adaptation intention will perceive greater levels of threat to tourism behaviours, as well as higher effectiveness in adaptive measures. We confirmed that the proposed theoretical framework for tourists' adaptation intention toward climate change is useful; the framework also sheds light on tourists' acknowledgement of hypothetical alterations in destination attractiveness caused by climate change, in addition to their psychological adaptations. We discuss theoretical and practical implications.